Influence of biomass ash additive on fusion characteristics of high-silicon-aluminum coal ash. (15th December 2020) - Zhang, Linmin; Wang, Jiaofei; Song, Xudong; Bai, Yonghui; Yao, Min; Yu, Guangsuo
Highlights: The effect of CDA on ash fusion behavior of high-silicon-aluminum coal was discussed. Mullite with a skeleton structure was the main reason for high AFTs of SHA. By adding CDA, low-melting-temperature minerals, anorthite and chlorapatite formed. The melting flow behavior of ash was studied by in-situ visualization technique. Abstract: The influence of cow dung ash (CDA) additive on the ash fusion characteristics of high-silicon-aluminum coal ash (SHA) was investigated using ash fusion temperature analyzer (AFTA), X-ray diffraction (XRD), thermogravimetric analyzer (TG-DSC) and FactSage thermodynamics software. In order to clarify the shrinkage/expansion and flow behavior of ash, high-temperature heating stage coupled with optical microscope (HSOM) was used to record the morphological change of ash in the heating process. The results show that the ash fusion temperatures (AFTs) decreased firstly and then increased with the addition of CDA. There was a minimum value of AFTs when the addition amount of CDA was 60%. Due to the high content of silicon and aluminum in SHA, the mullite with skeleton structure became the main crystalline phase in molten ash, which led to the high AFTs of SHA. The addition of CDA resulted in the increase of calcium and phosphorus in coal ash. Consequently, low-melting-temperature minerals such as anorthite and chlorapatite, which were responsible for the decrease in AFTs of blended ash, would be formed. With the continuous addition of CDA, the decrease of amorphous content led to the increase of AFTs. According to the results of ash fusion characteristics, SHA melting process only underwent the sintering stage due to the high AFTs, and its ash fusion behavior followed "softening-melting" mechanism. For CDA and blended ash (60% CDA), the melting process went through the sintering and melting stages, and the ash fusion behavior followed the "melting-dissolution" mechanism.